DRY NEEDLING IN MYOGENOUS TEMPOROMANDIBULAR DISORDERS: CURRENT EVIDENCE AND CLINICAL PERSPECTIVES FOR DENTAL AND PHYSIOTHERAPEUTIC PRACTICE - A NARRATIVE REVIEW - Weronika Kwaśnica; Zuzanna Jeziorska; Bartosz Szymajda; Zuzanna Galicka; Justyna Polko; Izabela Migdał; Jakub Artur Czapkiewicz; Maja Witek; Tomasz Horodniczy; Katarzyna Raczek (Archiv Euromedica, 2026)
Background Myogenous temporomandibular disorders are characterized by masticatory muscle pain, tenderness, and impaired mandibular function. Dry needling is used as a local intervention for myofascial pain, but its clinical effectiveness, safety, patient selection criteria, and place within conservative management remain uncertain. Aim This narrative review critically synthesizes current evidence on the effectiveness and safety of dry needling in myogenous temporomandibular disorders, with particular attention to pain outcomes, mandibular function, patient selection, methodological limitations, and its potential role within interdisciplinary conservative management. Materials and methods A SANRA-oriented narrative review was conducted. Literature was identified through searches of PubMed/MEDLINE, Scopus, Web of Science, Embase, and Google Scholar, supported by citation tracking. Systematic reviews, meta-analyses, randomized and controlled clinical trials, clinical guidelines, narrative reviews, scoping reviews, and other clinically relevant studies were considered. Forty publications were included in the final narrative synthesis. Results Current evidence suggests that dry needling may provide short-term reductions in pain intensity and pressure sensitivity and may improve selected measures of mandibular function. However, the magnitude, clinical relevance, and durability of these effects remain uncertain because of small samples, heterogeneous diagnostic criteria, variable treatment protocols, different comparator interventions, and short follow-up periods. Standardized criteria for patient selection have not been established. Conclusions Dry needling may be considered a potentially useful adjunct within conservative and interdisciplinary management of myogenous temporomandibular disorders. It should not be regarded as a universal or stand-alone treatment. Its optimal position in the treatment pathway and its superiority over botulinum toxin type A or other active interventions have not been established.